Investigation of Citric Acid By-Products from Rice Produced by Microbial Fermentation on Growth Performance and Villi Histology of Thai Broiler Chicken (KKU 1) - Mutyarsih Oryza.S (MDPI AG, 2021)
This study was conducted with Thai broiler chicken (KKU 1) to investigate the effect of citric acid by-products from rice (CABR) on growth performance and villi histology. A total of 192 broiler chicks were subject to three dietary treatments, including 0% CABR, 3% and 6% of dry matter. Body weight gains, feed intake, feed conversion ratio, survival rate, and production index (body weight gain, feed intake, feed conversion ratio, survival rates, and productive index, respectively) were considered for growth performance evaluation. Villi height (µm), crypt depth (µm), and villi: crypt ratio were recorded for the villi histological measurement. The performance did not show a significant effect when compared with the control group during at ages ranging from 1 to 56 days. Villi histology indicate a significant effect on villi height (µm), crypt depth (µm), and villi: crypt of broiler chicks compared with the control group. Also, the use of 3% CABR caused a reduction microbial contamination in chicken fecal matter. In conclusion, supplementation of CABR had no negative effects on growth performance of Thai broiler chicken (KKU 1). Also, the addition of 3% CABR to the feed might help reduce fecal microbial contamination and affect the villi histology of Thai broiler chickens (KKU 1).